Effect of Field Dodder (Cuscuta campestris Yunck.) on Tea Clones’ Growth Parameters and Yield in Nandi County, Kenya - Yego, M. J.; Mwasi, S. M.; Sudoi, V.; Cheramgoi, E. (Africa Environmental Review Journal, 2022)
Plants of the genus Cuscuta, commonly known as dodder belong to the family of Cuscutaceae and consists of about 200 species found almost everywhere in the world. A study was conducted to assess the effect of Cuscuta on tea leaf count, leaf area, trunk diameter and harvest biomass (yield). The study was laid out in a complete random design with three replicates. The twigs of Cuscuta campestris (3 twigs of 11-inch length) were collected from infected tea plants at Nandi hills tea Estates and were used to infect potted tea plants at the Tea Research Institute. The Cuscuta campestris significantly affected trunk diameter of clone TRFK 306 by increasing its diameter, reducing leaf area of clones TRFK 31/8 and TRFK 301/4 compared with the control. Mean leaf area for the infected clone TRFK306/1 (40.33±6.50) was significantly different (t=-3.01, p=0.04) from the control mean (46.00±14.00). Mean number of infected leaves of TRFK 303/577 clone was highest (73.00±5.29) followed by EPK TN14-3 (61.66±4.72). For the effect of Cuscuta campestris on tea harvest biomass, differences in mean control and mean infected harvest biomass was assessed. All the six clones showed a significant difference between the biomass means of infected and control. These results indicate that there may be varietal preference in the attack by the parasite.